Alternatives for the Treatment of Schistosomiasis: Physico-Chemical Characterization of an Inclusion Complex Between Praziquantel and Hydroxypropyl-beta-Cyclodextrin - Chaves, Izabel S.; Rodrigues, Stella G.; Melo, Nathalie F. S. [UNESP]; de Jesus, Marcelo B.; Fraceto, Leonardo F. [UNESP]; de Paula, Eneida; Pinto, Luciana M. A. (Colegio Farmaceuticos Provincia de Buenos Aires, 2010)
"Alternatives for the Treatment of Schistosomiasis: Physico-Chemical Characterization of an Inclusion Complex Between Praziquantel and Hydroxypropyl-beta-Cyclodextrin". Praziquantel (PZQ) is the drug of choice commonly used for the treatment of shistosomiasis. However, it has low aqueous solubility, which could limit its bioavailability in the body. To circumvent these features, an inclusion complex with hydroxypropyl-beta-cyclodextrin (HP-beta-CD) was prepared. Thus, the objective of this work was to prepare and characterize the PZQ/HP-beta-CD inclusion complex. Morphological, spectroscopic, and calorimetric analysis showed the first signs of the guest/host interaction. The complexation kinetic analysis was used to determine the kinetic constant and, besides that, it was possible to establish the time consumed to reach equilibrium. Using the solubility isotherm, it was observed that the interaction with HP-beta-CD increased 2.4 fold the aqueous solubility of plain PZQ. In vitro cytotoxicity tests, using fibroblast cells, evidenced no toxicity for these cells at the concentrations tested. These results demonstrated that there is a potential use of PZQ in formulations with HP-beta-CD.
Keywords: Cyclodextrin; Inclusion complex; Praziquantel; Schistosomiasis